Uterine sliding sign: a simple sonographic predictor for presence of deep infiltrating endometriosis of the rectum. (28th May 2013) - Hudelist, G.; Fritzer, N.; Staettner, S.; Tammaa, A.; Tinelli, A.; Sparic, R.; Keckstein, J.
ABSTRACT Objective To evaluate whether the presence of uterorectal adhesions demonstrated by transvaginal sonography (TVS) could aid as a simple sonographic predictor for deep infiltrating endometriosis (DIE) of the rectum in patients with symptoms suggestive of endometriosis. Methods This was a prospective multicenter study of women scheduled for laparoscopy because of symptoms suggestive of endometriosis. Patients were assessed prospectively using TVS before laparoscopy and radical resection of disease followed by histological confirmation. Sensitivity, specificity, positive (PPV) and negative (NPV) predictive values, accuracy and positive (LR+) and negative (LR−) likelihood ratios were calculated for the observation of a negative uterine 'sliding sign' on TVS in predicting the presence of DIE of the rectum. Results In total, 117 patients underwent laparoscopy and resection. Thirty‐four (29%) patients had DIE of the rectum. A negative sliding sign on TVS predicted DIE of rectum with a sensitivity of 85%, specificity of 96%, PPV of 91%, NPV of 94%, accuracy of 93.1%, LR + of 23.6 and LR– of 0.15. Conclusions Sonographic demonstration of uterorectal adhesions reflected by a negative uterine sliding sign is an easy and practical method for prediction of the presence of DIE involving the rectum. This could be a valuable 'red flag' sign for triaging patients to tertiary referral centers and specialized clinics for detailed investigation. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.